Selected References on Dynamometry - Strauss, G. R.
Selected References on Dynamometry (Isometric, Isokinetic, and Isotonic Modes of Exercise) Books on Muscle Physiology Books on Dynamometry Review Articles on Dynamometry Other Articles on Muscle and Dynamometry Kin-Com Reliability and Validity Reliability of Isokinetic Strength Testing - Elbow Reliability of Isokinetic Strength Testing - Knee Validity of Isokinetic Strength Testing - Knee Reliability of Isokinetic Strength Testing - Shoulder Reliability of Isokinetic Strength Testing - Trunk Reliability of Isokinetic Endurance Testing - Knee